Japanese cultural adaptation and validation of the social emotional health survey-secondary for junior high school students - Iida, Junko; Takizawa, Yu; Okayasu, Tomoko; Furlong, Michael J. (Frontiers in Education, 2024)
The Social Emotional Health Survey-Secondary (SEHS-S) assesses adolescents' psychological dispositions associated with positive psychosocial development. The present study extended SEHS-S research by validating the SEHS-S with a nonwestern sample of Japanese junior high school students (Grades 7-9; N = 1,181) and investigating sex and grade level difference in Covitality and four domains of positive psychological dispositions (Belief-in-Self, Belief-in-Others, Emotional Competence, and Engaged Living). The confirmatory factor analyses supported the internal validity of the SEHS-S with a second-order model. Higher Covitality scores predicted higher life satisfaction, school connectedness, and prosocial behavior and lower emotional symptoms, conduct problems, inattention/hyperactivity, and peer problems, evidence of concurrent validity. Analyses supported the factorial invariance for different sex and grade level. Females reported higher Belief-in-Others and Emotional Competence and lower Belief-in-Self and Engaged Living than males. Grade 9 students reported higher Covitality, Belief-in-Self, Emotional Competence, and Belief-in-Others than Grade 8 students. These results support expanding the use of the SEHS-S as a universal wellness screener in Japanese junior high schools to identify the social-emotional strengths of all students. Further study needs to establish how to use the SEHS-S most effectively with Japanese junior high school students in a culturally sensitive manner.